Growth Indices and Economy of Feed Intake of Broiler Chickens Fed Changing Commercial Feed Brands at Starter and Finisher Phases - Orheruata, A.M.; Nwokoro, S.O.; Alufohai, G.O.; Omagbon, B.I. (International Journal of Poultry Science, 2006)
Growth and feed intake data obtained from broiler chickens were analyzed to determine the effect of changing commercial feed brands on broiler performance. Mean total weight gain, specific growth rate (SGR) and growth efficiency (GE) were influenced by treatment at both starter and finisher phases with birds receiving changing feed brands having higher values. Economics of feed intake showed that feed cost/kg, feed cost/bird and feed cost/kg gain were higher for birds fed changing commercial feed brands at both phases. However, feed to gain ratio was better for birds fed treatment 1 at starter phase and treatment 2 at finisher phase with value of 2.52 and 3.11 respectively. Highest revenue was obtained from birds in treatment 3 and 2 at the starter and finisher phases respectively. Results of growth curve parameter estimates showed that the asymptotic weight of birds increased with the length of frequency of change of feed with a difference of 155g between the control and other treatments. Farmers can therefore use other feed brands once a week as such practice will in no way be detrimental to growth but rather slightly increase growth of the birds.